A Participatory GIS for Marine Spatial Planning in the Grenadine Islands. Issue 1 (5th December 2017) - Baldwin, Kimberly; Mahon, Robin
Abstract: Marine spatial planning (MSP) is a strategic way of improving decision‐making and delivering an ecosystem approach to managing human activities in the marine environment. Notwithstanding the central role of human agency in these approaches, it is recognised that many times marine management has not been effective in part due to a failure to use all available sources of information and knowledge, particularly the local knowledge of the resources' users. The transboundary Grenadine Islands, which rely heavily on the marine environment for livelihoods, provide an example of a complex system where there is a high diversity of uses and all available information is needed for effective management. We illustrate how a participatory GIS approach can be applied as a sound basis for practically incorporating an ecosystem approach within marine spatial planning initiatives. Key benefits include effective data management, increased spatial understanding and the definition of critical areas across the Grenada Bank. We found the application of a PGIS approach to support spatially‐based ecosystem‐level analyses of the Grenada Bank to be conducted and presented in ways that could be expected to increase stakeholder understanding of information generated thus supporting marine governance.